Potensi Dakwah Di Media Sosial Tiktok: Peluang Tantangan Islam Di Era Digital - Syifa Aulia Rahmadhani; Dhamar Indra Pratama; Rifada Nur Az Zahra Putri; Ziana Nur Rochimah; Ahmad Rahman Ludiansyah (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
This journal discusses the potential and challenges of Islamic da'wah in the digital era, especially through social media. Technological transformation has changed the way da'wah communication is carried out, allowing broad and interactive access. The millennial generation is recognized as agents of change who can utilize social media to spread moderate and inclusive da'wah messages. Despite huge opportunities, challenges such as the spread of hoax content, extremism and lack of digital competence are recognized as risks. The research uses quantitative research which emphasizes collecting and analyzing numerical data from respondents to understand certain phenomena. This method involves designing a structured questionnaire for data collection. The research results provide insight into effective strategies for using digital media for da'wah and efforts to overcome potential challenges and risks. The importance of da'wah on social media in introducing Islamic teachings, preventing Islamophobia, educating the younger generation, creating inclusive da'wah, and establishing dialogue between religions is the focus of implementation. The implementation discussed is the spread of Islamic teachings through the Tiktok platform. This research is expected to make a major contribution to the development of contemporary Islamic teachings in the digital era.